Comprehensive Genomic Characterization Analysis Identifies an Oncogenic Pseudogene RP11-3543B.1 in Human Gastric Cancer - Chen, Xin; Chen, Zhenyao; Wu, Hao; Liu, Xianghua; Nie, Fengqi; Wang, Zhaoxia; Sun, Ming (Frontiers in Cell and Developmental Biology, 2021)
Background Gastrointestinal Cancer (GICs) is the most common group of malignancies, and many of its types are the leading causes of cancer related death worldwide. Pseudogenes have been revealed to have critical regulatory roles in human cancers. The objective of this study is to comprehensive characterize the pseudogenes expression profiling and identify key pseudogenes in the development of gastric cancer (GC). Methods The pseudogenes expression profiling was analyzed in six types of GICs cancer from The Cancer Genome Atlas RNA-seq data to identify GICs cancer related pseudogenes. Meanwhile, the genomic characterization including somatic alterations of pseudogenes was analyzed. Then, CCK8 and colony formation assays were performed to evaluate the biological function of RP11-3543B.1 and miR-145 in gastric cancer cells. The mechanisms of pseudogene RP11-3543B.1 in GC cells were explored via using bioinformatics analysis, next generation sequencing and lucifarese reporter assay. Results We identified a great number of pseudogenes with significantly altered expression in GICs, and some of these pseudogenes expressed differently among the six cancer types. The amplification or deletion in the pseudogenes-containing loci involved in the alterations of pseudogenes expression in GICs. Among these altered pseudogenes, RP11-3543B.1 is significantly upregulated in gastric cancer. Down-regulation of RP11-3543B.1 expression impaired GC cells proliferation both in vitro and in vivo. RP11-3543B.1 exerts oncogene function via targeting miR-145-5p to regulate MAPK4 expression in gastric cancer cells. Conclusion Our study reveals the potential of pseudogenes expression as a new paradigm for investigating GI cancer tumorigenesis and discovering prognostic biomarkers for patients.